Cross-linguistic investigations of nominalization patterns - Paul, Ileana (Linguistik aktuell ;, 2014)
"Patterns of nominalization in Blackfoot are surveyed. It is demonstrated that two of these patterns behave like nouns while two others only partially behave like nouns. Degrees of nominality are analyzed within the assumption that there is a universal syntactic spine, a hierarchically organized set of categories, which are not intrinsically specified for nominality or verbality. They are category-neutral. Different nominalization patterns (and degrees of nominality) reduce to different ways of introducing the nominalizer: it may be introduced by a dedicated morphological marker (nominalization via complementation), or it may be introduced as part of the higher head (nominalization via selection). Category-neutral functional projections as well as functors are independently attested."--Provided by publisher